2011
DOI: 10.1111/j.1943-278x.2010.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Responses to a Suicidal Crisis: Implications for Suicide Prevention

Abstract: We conducted a cross-sectional, random-digit-dial survey to evaluate public responses to a hypothetical question: "If someone you knew was suicidal, what would you do first?" Younger people were more likely to call a suicide hotline, and less likely to go to an emergency room (ER) or call 911; immigrants (in the U.S. < 15 years) were more likely to call 911, and less likely to call a suicide hotline; African Americans were more likely to go to the ER and call 911; Hispanics were more likely to call 911 but les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Hispanic adults who report suicide ideation or attempts are also less likely than non-Hispanic Whites to have sought or received psychiatric services in the past year [39]. Furthermore, during a suicide crisis, Hispanics are less likely than non-Hispanics to use a crisis line [40].…”
Section: Suicide Prevention Interventions Among Hispanicsmentioning
confidence: 99%
“…Hispanic adults who report suicide ideation or attempts are also less likely than non-Hispanic Whites to have sought or received psychiatric services in the past year [39]. Furthermore, during a suicide crisis, Hispanics are less likely than non-Hispanics to use a crisis line [40].…”
Section: Suicide Prevention Interventions Among Hispanicsmentioning
confidence: 99%
“…In fact, 45.7% of Hispanic suicide attempters reported that they did not seek or receive psychiatric services in the year prior to attempting suicide, compared to 24.1% of non-Latino White attempters (Suicide Prevention Resource Center, 2013). Furthermore, Latinos are less likely than other ethnic groups to call a crisis line during a suicidal crisis (Larkin, Rivera, Xu, Rincon, & Beautrais, 2011).…”
Section: B Underutilization Of Mental Health Treatment By Latino Immmentioning
confidence: 99%
“…Also, frequently, there is a lower quality of care for Hispanics and a shortage of qualified professionals where Hispanic adults often seek assistance from primary care physicians for mental health issues (who may not be well trained in the area of mental health and suicide prevention) [ 30 , 31 , 36 41 ]. In response to the question “if someone you know was suicidal, what would you do first?”, a sample of Hispanic adults were most likely to recommend a psychiatrist (54%), talk to the family (63%), or contact a suicide hotline (50%) [ 38 ]. Also, two-thirds (65%) preferred to communicate in Spanish.…”
Section: Discussionmentioning
confidence: 99%